Osteonecrosis in the both femoral heads in a patient with Neuro-Behcet's Disease - Varoglu, Asuman Orhan; Aksoy, Asude (Professional Medical Publications, 2017)
Neuro-Behget's disease (NBD) is a rare clinical entity that frequently presents neuro-psychiatric symptoms, and mesodiencephalic and pontobulbar lesions. There is only one published report about osteonecrosis in NBD. We report a patient whose first presentation was neurological NBD with presenting bilateral femoral heads osteonecrosis. A 36-year-old male was hospitalized with gait disorder, diplopia and speech disorder. The past medical history of the patient was unremarkable. The MR image showed mesencephalic lesion with oedemaas a hyperintense area. The present case was diagnosed as NBD and treated with methylprednisolone (1g/day) only for five days. One year after, bilateral hip pain developed. MR image of both hips showed well-demarcated areas of osteonecrosis in the bilateral femoral heads. The patient was operated by an orthopedic surgeon. Because early diagnosis and immediate treatment of osteonecrosis is very important, the physician must bear in mind that osteonecrosis might result from impaired microvascular involvement in even NBD.
Keywords: Neuro-Behcet's Disease (NBD); osteonecrosis; both femoral heads